Railroad and road salt: a journey through the cities of Rosalía de Castro between 1859 and 1863 - García Vega, Lucía (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2013)
Our intention in this article is to advance a little more about the relationship that the biographical and bibliographical writer Rosalía de Castro (1837- 1885) could have established with three of the cities where she lived between 1859 and 1863
Keywords: Rosalía de Castro; urban space; Madrid; Santiago de Compostela; Vigo; Cádiz